Newborn dopaminergic neurons are associated with the migration and differentiation of SVZ-derived neural progenitors in a 6-hydroxydopamin-injected mouse model. (3rd June 2017) - Xie, M.Q.; Chen, Z.C.; Zhang, P.; Huang, H.J.; Wang, T.T.; Ding, Y-Q.; Qi, S.S.; Zhang, C.; CHEN, S.X.; Zhou, P.; Shao, C.C; Liao, M.; et al.
Highlights: Assess the regenerative capacity of NPCs following 6-hydroxydopamine injection. Investigate the proliferation and differentiation of LV-, 3V-, or Aq-SVZ- and midbrain-derived NPCs. Trace the origin of SN newborn dopaminergic neurons. 6-hydroxydopamine injection induced an incomplete recovery in the nigrostriatal system. SN newborn dopaminergic neurons might derive from 3V- and Aq-SVZ NPCs. Abstract: The use of the existing endogenous neural progenitor cells (NPCs) in the brains of adult mammalian animals is challenging for cell therapy in treating Parkinson's disease (PD). Previous studies have indicated that there is a low level of neurogenesis in the substantia nigra (SN) of adult mice. To assess the regenerative/neurogenic capacity of NPCs following an intranigral injection of 6-hydroxydopamine (6-OHDA), the proliferation and differentiation of subventricular zone (SVZ)- and midbrain-derived NPCs were investigated, and the origin of SN newborn dopaminergic neurons was traced by using Nestin-CreER TM ::ROSA26-LacZ mice and constructing a plasmid CD133-Promoter2-Cre. Our results showed that an intranigral injection of 6-OHDA-induced loss of dopaminergic neurons produced a significant increase in the SVZ-derived NPCs of the third ventricle (3V), cerebral aqueduct (Aq), and their surrounding regions. The SN newly generated dopaminergic neurons might contribute a little to an incomplete recovery of the nigrostriatal system. In addition, we found that SN newborn dopaminergic neurons were mainly derived from the migration and differentiation of the NPCs in the 3V- and Aq-SVZ and their adjacent regions. Thus, it will become an ideal strategy to treat PD by promoting the proliferation and differentiation of endogenous NPCs.